Impact of the COVID‐19 crisis on healthcare workers: The need to address quality of working life issues. Issue 6 (26th April 2022) - Marcellin, Fabienne; Cousin, Lorraine; Di Beo, Vincent; Mahé, Véronique; Rousset‐Torrente, Olivia; Carrieri, Patrizia; Chassany, Olivier; Duracinsky, Martin
Abstract : See related Reply